2023
DOI: 10.1007/s10653-023-01585-w
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for environmental biogeochemistry and food security for aquaculture around Lake Victoria, Kenya

Abstract: The impact of population expansion through economic growth and development has been identified as one of the key drivers of both water and sediment contamination from potentially harmful elements (PHEs). This presents a major hazard not only to aquatic ecosystems but local riparian communities and beyond who rely heavily on this natural resource for drinking water and fish—a valuable source of dietary micronutrients and protein. The present study measured biogeochemical concentration of PHEs in water, sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Forero-Cantor et al 10 in their study in Ukerewe and Muleba observed some variation in food security. Marriott et al 9 observed that food security and nutritional cases varied across households and time.…”
Section: Status Of Food Security and Nutrition In The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Forero-Cantor et al 10 in their study in Ukerewe and Muleba observed some variation in food security. Marriott et al 9 observed that food security and nutritional cases varied across households and time.…”
Section: Status Of Food Security and Nutrition In The Study Areamentioning
confidence: 99%
“…It is through this fact that, Cochrane & D'Souza 7 observed that policies to address food insecurity in Tanzania have frequently been hindered by a lack of accurate estimates of production and existing food needs. Apart from this weakness, it has also been evident that cases of food and nutritional security vary across regions and time 7,9,10 . In this case, obtaining more refined and up-to-date evidence-based information is inevitable for undertaking informed decisions.…”
Section: Introductionmentioning
confidence: 99%